The functional role of sulforaphane in intestinal inflammation: a review. Issue 2 (22nd December 2021) - Wei, Li-Yang; Zhang, Jiu-Kai; Zheng, Lei; Chen, Ying
Abstract : The preventive and interventional effects of sulforaphane on intestinal inflammation are shown. Abstract : Intestinal inflammation represented by inflammatory bowel disease (IBD) has become a global epidemic disease and the number of patients with IBD continues to increase. This digestive tract disease not only affects the absorption of food components by destroying the intestinal epithelial structure, but also can induce diseases in remote organs via the gut–organ axis, seriously harming human health. Nowadays, increasing attention is being paid to the nutritional and medicinal value of food components with increasing awareness among the general public regarding health. As an important member of the isothiocyanates, sulforaphane (SFN) is abundant in cruciferous plants and is famous for its excellent anti-cancer effects. With the development of clinical research, more physiological activities of SFN, such as antidepressant, hypoglycemic and anti-inflammatory activities, have been discovered, supporting the fact that SFN and SFN-rich sources have great potential to be dietary supplements that are beneficial to health. This review summarizes the characteristics of intestinal inflammation, the anti-inflammatory mechanism of SFN and its various protective effects on intestinal inflammation, and the possible future applications of SFN for promoting intestinal health have also been discussed.